2017
DOI: 10.1177/1077699016687724
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survivors’ Contribution to Psychosocial Adjustment of Newly Diagnosed Breast Cancer Patients in a Computer-Mediated Social Support Group

Abstract: This study investigated the role of breast cancer survivors in a computer-mediated social support (CMSS) group for women with breast cancer. Applying a computer-aided content analytic method, the present study examined the differences in support provision between survivors and newly diagnosed patients. This study further investigated the impacts of survivor-provided social support on psychosocial adjustment of newly diagnosed patients. The results revealed that, compared with newly diagnosed patients, breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 93 publications
(137 reference statements)
0
20
0
Order By: Relevance
“…In a previous intervention, patients with non–small cell lung cancer who partook in an online support group, as opposed to those who only had access to internet articles, experienced fewer symptoms of distress [29]. Another intervention found that newly diagnosed breast cancer patients who received support from breast cancer survivors in an online forum reported improved quality of life and decreased depression [30]. Study trials are being designed to create Web-based portals for older adults who often suffer from isolation; early findings have demonstrated potential benefits [31].…”
Section: Affordances To Consider In Intervention Designmentioning
confidence: 99%
“…In a previous intervention, patients with non–small cell lung cancer who partook in an online support group, as opposed to those who only had access to internet articles, experienced fewer symptoms of distress [29]. Another intervention found that newly diagnosed breast cancer patients who received support from breast cancer survivors in an online forum reported improved quality of life and decreased depression [30]. Study trials are being designed to create Web-based portals for older adults who often suffer from isolation; early findings have demonstrated potential benefits [31].…”
Section: Affordances To Consider In Intervention Designmentioning
confidence: 99%
“…Some studies report that social support is related to psychosocial adjustment among patients with breast cancer (Kim & So, 2012; Leung, Pachana, & McLaughlin, 2014; Yang & Kim, 2016). Environmental resources such as social support have a positive association with psychosocial adjustment in BCS (Moon, Chih, Shah, Yoo, & Gustafson, 2017). In other words, social support is an important coping resource that enhances adjustment among BCS (Jang & Kim, 2018; Kim & So, 2012; Lazarus & Folkman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 72% of adults seek health information on the Web, and 16% search for peers with similar health concerns [1]. Online communities can effectively extend health education [2,3] and facilitate social support [3,4] and have been linked to improved self-management [2] and enhanced health outcomes [3]. The number of online communities has grown substantially over the past decade, with countless websites increasing traffic from patients and caregivers through user-engaged communities [5].…”
Section: Introductionmentioning
confidence: 99%